Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1071/sr21022
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics and tillage can predict the effect of ‘structure lime’ on soil aggregate stability

Abstract: Context. In Sweden, mixtures of 80-85% ground limestone and 15-20% slaked lime (hereafter, 'structure lime') are used in subsidised environmental schemes to improve aggregate stability and mitigate phosphorus losses on clay soils. Aims. This study investigated different rates of structure lime application and soil variables on aggregate stability on clay soils, and whether soil properties can predict aggregate stability following structure liming. Methods. Increasing application rates of 0-16 t ha −1 of struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…In a previous study examining the effect on turbidity approximately one year after structure liming at the eight trials used in the present study together with another 22 field sites, we found that structure liming had the most pronounced short-term effect on soils with high clay content and low initial pH (Blomquist et al 2022). Therefore, Rel.…”
Section: Aggregate Stabilitysupporting
confidence: 46%
See 3 more Smart Citations
“…In a previous study examining the effect on turbidity approximately one year after structure liming at the eight trials used in the present study together with another 22 field sites, we found that structure liming had the most pronounced short-term effect on soils with high clay content and low initial pH (Blomquist et al 2022). Therefore, Rel.…”
Section: Aggregate Stabilitysupporting
confidence: 46%
“…In fact, the variation seen indicates a need for a site-specific application strategy and for soil characteristics to be taken into consideration. In a previous study, we observed this type of interaction between liming treatment and trial in the short term (Blomquist et al 2022) and suggested that the interaction derives from soil properties such as clay content and soil organic matter, clay mineralogy, initial pH and management factors such as tillage before and after structure liming.…”
Section: Decreasing Aggregate Stabilitymentioning
confidence: 64%
See 2 more Smart Citations
“…Aggregate stability testing, as described in Blomquist et al (2022), was performed on soil samples from the top layer (0−5 cm), which were sieved to obtain samples of the 2−5 mm aggregate fraction. The samples were airdried and then subjected to simulated rainfall in two events, with 24 h between events.…”
Section: Sampling and Analyses Of Soilmentioning
confidence: 99%